2006
DOI: 10.1111/j.1528-1167.2006.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of Anticonvulsant Medication after Epilepsy Surgery in Children

Abstract: Summary:Purpose: To evaluate the long-term outcome of medication-reduction/discontinuation trials after epilepsy surgery in pediatric patients.Methods: Of the total Bonn pediatric surgical sample (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001); n = 251), we were able to obtain postsurgical follow-up data for 232 patients. We surveyed 140 of these patients by using a standardized telephone interview that addressed medicationreduction/discontinuation trials.Results: Of the 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 9 publications
3
11
2
10
Order By: Relevance
“…Therefore, the advantageous seizure outcome in younger patients provides indirect evidence for the concept of epileptogenic network formation in previously non-epileptogenic tissue during the course of uncontrolled epilepsy 27. Studies on AED withdrawal after successful focal epilepsy surgery similarly suggest a higher rate of seizure freedom with no further need for AEDs in younger patients with shorter epilepsy duration as compared with adult patients 28. Evidently, the obtained age-at-surgery effect on seizures requires confirmation from other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the advantageous seizure outcome in younger patients provides indirect evidence for the concept of epileptogenic network formation in previously non-epileptogenic tissue during the course of uncontrolled epilepsy 27. Studies on AED withdrawal after successful focal epilepsy surgery similarly suggest a higher rate of seizure freedom with no further need for AEDs in younger patients with shorter epilepsy duration as compared with adult patients 28. Evidently, the obtained age-at-surgery effect on seizures requires confirmation from other groups.…”
Section: Discussionmentioning
confidence: 99%
“…(2004), we could gather seven studies that primarily addressed AED withdrawal after epilepsy surgery. Three of them addressed epilepsy surgery outcome in the pediatric age group (Hoppe et al., 2006; Sinclair et al., 2007; Lachhwani et al., 2008), and one study comprised patients who underwent temporal and extratemporal resections (Park et al., 2010). The remaining three studies investigated the seizure outcome and the factors that influenced the outcome of patients with temporal lobe epilepsy (Kim et al., 2005; Al‐Kaylani et al., 2007; Lee et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…17,26 The number of reoperations, and eventual seizure-free patients off medications with longer follow-up durations, are similar between our series and the literature. 10,[27][28][29][30] Phase II intracranial EEG studies were used at a lower rate than usually reported. The ILAE survey of 20 pediatric epilepsy surgery centers involving 543 children found that intracranial electrodes were used in 27% of patients.…”
Section: Methodsmentioning
confidence: 99%